2021
DOI: 10.1111/hiv.13212
|View full text |Cite
|
Sign up to set email alerts
|

HCV reinfection after HCV therapy among HIV/HCV‐coinfected individuals in Europe

Abstract: The members the EuroSIDA study group are given in the Appendix.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Compared with the highly varied reported incidence of HCV reinfection from 0% to 17% in HIV-positive patients, the incidence of HCV reinfection in our patients with treatment-induced SVR 12 was 4.02 per 100 PYFU, which was in line with a recent large-scale pan-Europe survey that demonstrated an overall incidence of HCV reinfection of 4.65 per 100 PYFU in HIV-positive patients who achieved SVR with IFN or DAA [ 21 ]. Because most patients were MSM, we further demonstrated the risk of HCV reinfection in our HIV-positive MSM to be 4.12 per 100 PYFU, which was also similar to a long-term cohort that reported an incidence of 3.85 per 100 PYFU in the Netherlands [ 18 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Compared with the highly varied reported incidence of HCV reinfection from 0% to 17% in HIV-positive patients, the incidence of HCV reinfection in our patients with treatment-induced SVR 12 was 4.02 per 100 PYFU, which was in line with a recent large-scale pan-Europe survey that demonstrated an overall incidence of HCV reinfection of 4.65 per 100 PYFU in HIV-positive patients who achieved SVR with IFN or DAA [ 21 ]. Because most patients were MSM, we further demonstrated the risk of HCV reinfection in our HIV-positive MSM to be 4.12 per 100 PYFU, which was also similar to a long-term cohort that reported an incidence of 3.85 per 100 PYFU in the Netherlands [ 18 ].…”
Section: Discussionsupporting
confidence: 86%
“…Although the risk of HCV reinfection of our HIV-positive patients was much higher than that of the reference patients, we found that no baseline factors predicted HCV reinfection [ 21 ]. Multiple sex partners, unprotected anal intercourse, group sex, sharing sex toys, and amphetamine abuse in HIV-positive MSM and ongoing use of cocaine, methamphetamine, or heroin injection in HIV-positive PWID after achieving SVR were highly associated with HCV reinfection; these factors were evident in our HIV-positive patients with HCV reinfection [ 17 , 20 , 24 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, γδ T- and B-cell activation remained at higher levels in HIV-HCV co-infection than that which was measured in HCV mono-infection alone. Given the enduring clinical risk of cART-treated HIV-infected subjects [ 23 ] and the high rates of subsequent HCV re-infection in this population [ 30 ], future studies are needed to elucidate the impact of DAA therapy on long-term immune imbalances in HIV-HCV co-infected individuals.…”
Section: Discussionmentioning
confidence: 99%